Resolving Inclusion Structure and Deformation Mechanisms in Polylactide Plasticized by Reactive Extrusion. Issue 12 (14th November 2017) - Brüster, Berit; Amozoqueño, Camilo; Grysan, Patrick; Peral, Inma; Watts, Benjamin; Raquez, Jean‐Marie; Dubois, Philippe; Addiego, Frédéric
Abstract: A multiscale characterization approach is developed to resolve the structure of inclusions in polylactide (PLA) plasticized with acrylated poly(ethylene glycol) (acrylPEG) by reactive extrusion. Scanning transmission X‐ray microscopy (STXM) coupled with near‐edge X‐ray absorption fine structure (NEXAFS) nanospectroscopy demonstrates that these inclusions have a core–shell morphology. This technique also proves that the inclusions consist of polymerized acrylPEG (poly(acrylPEG)), which is also confirmed by elastic modulus measurement using an atomic force microscope. The shell consists of poly(acrylPEG)‐rich domains, while the core is less rich in the polymerized plasticizer. Upon drawing, the density of the inclusion's core and shell markedly decreases as shown by microcomputed X‐ray tomography measurements, and no inclusion–matrix debonding is observed. At the same time, sub‐micrometer cracks are noted between inclusions by STXM/NEXAFS imaging, which may result from the presence of crosslinking points restricting the local chain mobility. Novel knowledge about the reactive extrusion‐induced PLA structure is released. Abstract : The reactive plasticization of polylactide with acrylated poly(ethylene glycol) (acrylPEG) forms grafted inclusions inside the matrix. The inclusions exhibit a core–shell structure, where the core consisted of less dense poly(acrylPEG) than the shell. Upon drawing, the inclusions are stretched, while their density decreases at the shell and core regions. At the same time, sub‐micrometer cracks form between inclusions.